2020
DOI: 10.1021/acs.orglett.0c02239
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Functionalization of Benzylic C–H Bonds with N-Fluorobenzenesulfonimide: Switch from C–N to C–F Bond Formation Promoted by a Redox Buffer and Brønsted Base

Abstract: A copper catalyst in combination with N-fluorobenzenesulfonimide (NFSI) has been reported to functionalize benzylic C–H bonds to the corresponding benzylic sulfonimides via C–N coupling. Here, we reported a closely related Cu-catalyzed method with NFSI that instead leads to C–F coupling. This switch in selectivity arises from changes to the reaction conditions (Cu/ligand ratio, temperature, addition of base) and further benefits from inclusion of MeB­(OH)2 in the reaction. MeB­(OH)2 is shown to serve as a “red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The bis(phenyl)sulfonamide radical then abstracts a hydrogen atom from C(sp 3 )-H adjacent to nitrogen of compound 1 to generate the corresponding radical A. In Path I, a radical chain propagation process is proposed, which is supported by recent work on alkyl radical fluorination 51,52 , especially the work on fluorine transfer to alkyl radical from N-F reagents 51 reaction to generate the fluorination intermediate B 53,54 with regeneration of L/Cu(I) complex. Finally, the fluorinated intermediate B undergoes a nucleophilic substitution promoted by NH(SO 2 Ph) 2 via the iminium intermediate C to afford the final CDC product 2 with elimination of HF 54 .…”
Section: Synthetic Utilitiesmentioning
confidence: 98%
“…The bis(phenyl)sulfonamide radical then abstracts a hydrogen atom from C(sp 3 )-H adjacent to nitrogen of compound 1 to generate the corresponding radical A. In Path I, a radical chain propagation process is proposed, which is supported by recent work on alkyl radical fluorination 51,52 , especially the work on fluorine transfer to alkyl radical from N-F reagents 51 reaction to generate the fluorination intermediate B 53,54 with regeneration of L/Cu(I) complex. Finally, the fluorinated intermediate B undergoes a nucleophilic substitution promoted by NH(SO 2 Ph) 2 via the iminium intermediate C to afford the final CDC product 2 with elimination of HF 54 .…”
Section: Synthetic Utilitiesmentioning
confidence: 98%
“…Cu-catalyzed radical-relay reactions that use N-uorobenzenesulfonimide (NFSI) as the oxidant have expanded rapidly in recent years 19,[29][30][31][32][33][34][35][36][37][38][39] and offered a possible strategy to achieve C-H isocyanation as these methods oen support oxidative coupling with the C-H substrate as the limiting reagent. Several mechanistic features of these reactions merit consideration.…”
Section: Mechanistic Considerations and Reaction Optimizationmentioning
confidence: 99%
“…[35][36][37] A second mechanistic feature involves radical functionalization, which can proceed by several different pathways. Cu I can initiate radical-chain uorination of C-H bonds 36,37,[40][41][42][43] with NFSI, but Cu/NFSI methods more commonly promote oxidative coupling of C-H bonds with nucleophilic reaction partners (Nu ¼ CN, N 3 , OR, Ar, among others). The mechanism of coupling can vary and depends on the coupling partner (Fig.…”
Section: Mechanistic Considerations and Reaction Optimizationmentioning
confidence: 99%
“…It is noteworthy that 2 was obtained in quantitative yield even in the presence of HFIP since it was reported that an additive amount of HFIP can activate the benzylic fluorine group via hydrogen bonding. We attributed this to the hydrogen bonding interaction between the fluoride ion of CsF with HFIP, which decreased the interaction of HFIP with the benzylic fluoride.…”
mentioning
confidence: 91%